Manufacturing of Volumetric Glass–Based Composites with Single‐ and Double‐QD Doping. (15th November 2018) - Nowaczynski, Rafal; Gajc, Marcin; Surma, Hancza B.; Osewski, Pawel; Strzep, Adam; Ryba‐Romanowski, Witold; Pawlak, Dorota A.
Abstract: Quantum dot (QD)‐based light‐emitting materials are gaining increased attention because of their easily tunable optical properties desired for various applications in biology, optoelectronics, and photonics. However, few methods can be used to manufacture volumetric materials doped with more than one type of QD other than QD‐polymer hybrids, and they often require complicated preparation processes and are prone to luminescence quenching by QD aggregation and separation from the matrix. Here, simultaneous doping of a volumetric glass‐based nanocomposite with two types of QDs is demonstrated for the first time in a single‐step process using the nanoparticle direct doping method. Glass rods doped with CdTe, CdSe/ZnS, or co‐doped with both QDs, are obtained. Photoluminescence and lifetime experiments confirm temperature‐dependent double emission with maxima at 596 and 720 nm with mean lifetimes up to 16 ns, as well as radiative energy transfer from the short wavelength–emitting QDs to the long wavelength–emitting QDs. This approach may enable the simple and cost‐efficient manufacturing of bulk materials that produce multicolor luminescence with cascade excitation pumping. Applications that could benefit from this include broadband optical fiber amplifiers, backlight systems in LCD screens, high‐power LEDs, or down‐converting solar concentrators used to increase the efficiency of solar panels. Abstract : Quantum dots (QDs) of different structures are successfully incorporated into a single volumetric glass composite using a nanoparticle direct doping method. Sodium borophosphate glass in a form of a rod doped with CdTe QDs and CdSe/ZnS core–shell QDs simultaneously exhibits temperature‐dependent double‐color photoluminescence. Lifetime measurements indicate radiative energy transfer from CdSe/ZnS QDs to CdTe QDs.